15 Jahre Panelstudie zur (Medien-)Sozialisation Wie leben die Kinder von damals heute als junge Erwachsene? - Paus-Hasebrink, Ingrid (Lebensweltbezogene Medienforschung: Angebote - Rezeption - Sozialisation, 2021)
This book deals with the role of media in the period of transition from youth to adulthood. It thus continues the (media) socialisation study with socially disadvantaged children and their families, and follows on from the previous volumes in this series. What has happened to those children, who were five years old at the beginning of the study in 2005? How do young people position themselves in the face of new social challenges and new media offerings, in terms of not only their private lives, but also and in particular their professional careers? What courses of action and blueprints and capacity for action are now available to them as young adults? Furthermore, how are their closest attachment figures? On the basis of a 7th phase of research, which was conducted in 2020, this book deals with these questions.